Forage intake and behavior of goats on Tanzania-grass pasture at two regrowth ages - doi: 10.4025/actascianimsci.v35i1.16035 (Acta Scientiarum. Animal Sciences, 2012)
The forage mass, sward structure, the ingestive and grazing behavior and forage intake by goats grazing on Tanzania-grass at 22 and 37 days of regrowth were evaluated. A completely randomized experimental design was used, with eight replications for evaluating the pasture and bite depth, and six replications for evaluating intake, feeding and grazing behavior. The forage canopy height ranged from 64.1 to 92.7 cm. Higher forage mass was observed at 37 days, and the best leaf/stem ratio, at 22 regrowth days. The bite depth did not differ between regrowth ages. The biting rate for the 22 regrowth days (23.07 bites min.-1) was higher than at 37 days (19.06 bites min.-1). The grazing time was longer at the regrowth age of 22 days (5.58h) than at 37 days (4.51h). The average feed intake was 2.75% of the body weight and was not different between regrowth ages.